Built to beat chaos : biblical wisdom for leading yourself and others - Harpst, Gary (John Wiley & Sons, Inc., 2023)
"The world is a chaotic place. Always has been. And not only is the world itself chaotic, but chaos is a typical state inside organizations. 47% of executives say it is pervasive. People are overwhelmed by chaos, not realizing that we are designed (created) to overcome chaos. The Bible gives profound insights that show that we are all called to be leaders and bring order out of chaos in some part of our world. This is the only way we get fulfillment. Built to Beat Chaos is designed to broaden people's understanding of what chaos is and why and how we were created to overcome it. This book speaks to every person alive. Everyone is a leader"--